The updating of fantasy tale in rosa Montero’s children and juvenile literature - Villar Secanella, Eva María (Ondina - Ondine, 2020)
This article explores the links between Rosa Montero’s trilogy Las barbaridades de Bárbara, El viaje fantástico de Bárbara y Bárbara contra el Doctor Colmillos and the traditional fantasy tale. It analyses the way in which Montero updates traditional strategies in her search for complicity between the narrative discourse and a reader in development. The article also includes a brief didactic proposal exploring the tale’s potentiality aimed at encouraging reading habits and literary competency in young readers. Key words: tale, fantasy, literary competency, reading habit, reader in development, didactics